Дослідження методів планування при управлінні ІТ-проєктом стоматологічних поліклінік - Курченко, Є. А. (ХНУРЕ, 2025)
The specific features of the ІТ project for the dental clinic's health information system (HIS) have been identified. The role of planning as one of the stages of ІТ project development for the dental clinic and ІТs impact on the final result has been determined. The main risks and consequences of poor planning have been analyzed. Existing planning methods such as CPM, PERT, Monte Carlo, Fast Tracking, Crashing, and Resource Leveling have been reviewed in the context of their application in the development of the dental clinic's HIS. AddІТionally, their advantages and disadvantages have been identified.
Keywords: метод планування; стоматологія